H1N76/77 deamidation facilitates chromatin remodelling and genome stability during DNA damage repair - Tingting Feng; Mengyan Li; Chenmiao Hu; Yuan Tian; Wei‐Guo Zhu (Clinical and Translational Medicine)
Abstract Chromatin relaxation is a permissiven progress for DNA repair through enabling repair factors to access the damaged DNA. Linker histone H1 is important in maintaining chromatin compaction under physiological state. The recent evidence highlights the importance of H1 modifications in response to cellular stress. Following DNA double‐strand breaks, the metabolic enzyme phosphorylated CTP synthase 1 (CTPS1) functions as a deamidase, catalyzing the rapid conversion of H1 residues Asn76 and Asn77 into aspartate. This modification enables subsequent acetylation at Lys75 by the histone acetyltransferase p300, thereby reducing H1‐DNA affinity and promoting chromatin decompaction. This sequential modification‐H1 deamidation followed by acetylation‐facilitates the recruitment of repair factors involving both homologous recombination and non‐homologous end joining repair pathways, and consequently promoting DNA repair. Importantly, high expression of CTPS1 is associated with resistance to radiotherapy in mouse models and clinical cancer patients, suggesting that the CTPS1 may serve as a potential therapeutic target. While targeting CTPS1 may offer opportunities to enhance radiosensitivity of cancer patients, challenges related to specificity and off‐target effects require further studies. This article highlights an emerging role of H1 modification in the DNA damage repair and discusses the therapeutic potential of manipulating H1 deamidation in cancer treatment.